Maximum Thickness Location Selection of High Subsonic Axial Compressor Airfoils and Its Effect on Aerodynamic Performance - Tao, Chuansijia; Du, Xin; Ding, Jun; Luo, Yizhou; Wang, Zhongqi (Frontiers in Energy Research, 2021)
Solidity and camber angle are key parameters with a primary effect on cascade diffusion. Maximum thickness location has a considerable impact on blade loading distribution. This paper investigates correlations of maximum thickness location, solidity, and camber angle with cascade performance to choose maximum thickness location quickly for compressor cascades with different diffusion. The effects of maximum thickness location, solidity, and camber angle on incidence characteristics are discussed based on abundant two-dimensional cascade cases computed through numerical methods. Models of minimum loss incidence, total pressure loss coefficient, diffusion factor, and static pressure rise coefficient are established to describe correlations quantitatively. Based on models, dependence maps of total pressure loss coefficient, diffusion factor, and static pressure rise coefficient are drawn and total loss variation brought by maximum thickness location is analyzed. The study shows that the preferred selection of maximum thickness location can be the most forward one with no serious shock loss. Then, the choice maps of optimal maximum thickness location on different design conditions are presented. The optimal maximum thickness locates at 20-35% chord length. Finally, a database of optimal cases which can meet different loading requirements is provided as a tool for designers to choose geometrical parameters.